THE MIDDLE EOCENE IN THE ALPINE RETROFORELAND BASIN (NORTHERN ITALY): SEDIMENTARY RECORD OF A “MESO-ALPINE” ARC-TRENCH SYSTEM IN THE ALPS - Sciunnach, Dario; Tremolada, Fabrizio; Premoli Silva, Isabella; Scardia, Giancarlo [UNESP] (Milano University Press, 2023)
The middle Eocene Cibrone Formation of Brianza (central-western Lombardy) represents an important stratigraphic record to understand a key step of the tectonic evolution of the Alpine range poorly recorded elsewhere. Quantitative petrographic analysis of turbidite arenites, well-constrained in age by the biostratigraphy of interlayered marlstones based on calcareous foraminifera and nannoplankton, allowed us to identify a possible vertical compositional trend within the Cibrone Fm. and to document the NP17 nannofossil Zone (Bartonian) in central Lombardy exposures, east of the Ternate Formation outcrop area. Variable arenite compositions are interpreted to reflect contributions from different source areas, i.e., recycled orogen, island arc, and starved continental shelf. In a paleogeographic scenario still open to different interpretations, the proposed reconstruction supports a classical plate tectonics model for arc-trench systems. The stratigraphic gap, recorded everywhere in Lombardy, between the Eocene succession and the base of the Gonfolite Lombarda Group (upper NP24 nannofossil Zone, early Chattian), corresponds to the earliest stage of continental collision, uplift and erosion that climaxed in the Neo-Alpine Phase.
Keywords: Alpine Orogeny; arenite petrography; biostratigraphy; calcareous nannofossils; Eocene; foraminifera; Southern Alps